Management Boarding School SMAIT: Character Education Religious and Disciplined - Mirnawati (Zabags Qu Publish, 2024)
Abstract: This study aims to examine the management of the boarding school program in shaping religious character and discipline at SMA IT Ash-Shiddiiqi. Utilizing a phenomenological approach and qualitative methods, the research collected data from primary and secondary sources through observation, interviews, and documentation. Data analysis was conducted through data collection, reduction, presentation, and conclusion drawing, with data validity tested using credibility, transferability, dependability, and confirmability. The findings indicate that the planning process for the boarding school program involves a forum of discussions among the foundation, educators, madrasah committee, guardians of students, and dormitory managers. Program organization includes structural task assignments. The habituation of religious culture and discipline takes place in both the dormitory and school environments. Program control is carried out through regular evaluations of each activity and monthly assessments with the program managers. Supporting factors for program management include dormitory and classroom facilities, the presence of musyrif/ah accompanying the students, collaboration between parents and teachers, and a strong desire for knowledge. However, there are hindering factors, such as a decline in individual commitment, which is reflected in mischief, boredom, and laziness among students due to the heavy workload. Thus, the management of the boarding school at SMA IT Ash-Shiddiiqi proves effective in fostering students' religious character and discipline, although attention is needed for the existing hindering factors.